Question about Computers & Internet

Open Question

(2y)(4y cubed) +(3y squared)(5y squared)

Multiplying monomials

Posted by Anonymous on

Ad

6 Suggested Answers

6ya6ya
  • 2 Answers

SOURCE: I have freestanding Series 8 dishwasher. Lately during the filling cycle water hammer is occurring. How can this be resolved

Hi,
a 6ya expert can help you resolve that issue over the phone in a minute or two.
best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).
click here to download the app (for users in the US for now) and get all the help you need.
goodluck!

Posted on Jan 02, 2017

Ad
  • 3 Answers

SOURCE: Solving matrix

Go to your matrix button and enter a "3x4" matrix.

Then enter it as follows:

-3 4 5 7
4 3 2 9
-5 5 3 -10

Then exit out and go to "2nd->matrix->math->rref(". Then press enter.

Your screen should look like this:

rref(

Then go to matrix and select your 3x4 matrix, press enter and close it with a parathesis. Your screen should look like this:

rref([A])

Press enter and the screen should say this:

1 0 0 2
0 1 0 -3
0 0 1 5

So,
x=3
y=-3
z=5

Hope this cleared up the confusion!

SJ_Sharks

Posted on Mar 14, 2009

Ad
  • 102 Answers

SOURCE: x-3y=5

2y - x = 3
x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is x = 1, y = 2

or in ordered pair notation (1, 2)

Posted on Jun 29, 2009

  • 269 Answers

SOURCE: [y-{2y-(5y-1)/3}={(y-1)/3}+1/2]

gif&s=3 mel

Posted on Sep 17, 2010

  • 7993 Answers

SOURCE: How do you use a fx-9750GII calculator and inverse

One not way would be to define a 4x4 matrix Mat A to hold the coefficients of the linear system. Then define a 4x1 column vector Mat V to hold the constants on the right.
Define a third 4x4 matrix Mat B you may leave filled with 0.
On command line, in Run Mat screen enter (Mat A) ^(-1) and store it in the zero-filled matrix Mat B. this is the inverse of Mat A.
If the inverse of Mat A exists, and it does in this case, the solution of the system is obtained as the column vector, resulting from the multiplication of Mat B by column vector Mat V

You can even shorten the procedure by just calculating ((Mat A)^-1)X (Mat V) [EXE]

To summarize

  1. Create 4x4 Mat A and type in the coefficients of the linear system.
  2. Create a 4x1 column vector Mat V for the right-hand sides
  3. Obtain you solution vector as ((Mat A)^-1)X (Mat V) [EXE]
To get the Mat identifier on command line,
  • use catalog or
  • in RunMat screen, press [OPTN] followed by [F2:Mat], then [F1:Mat].
  • At this point the identifier is on command line, and you have to press [ALPHA] [X,Theta, T] to enter letter A.
  • You use a similar key sequence to enter Mat V
To calculate the inverse of the matrix just use the [SHIFT][)] key sequence which is (X^-1)
Multiplication operator is the regular [times] key.

Posted on Nov 16, 2010

  • 1 Answer

SOURCE: does the program do order of operations

(9-5+(7-2).4)=24

Posted on Sep 07, 2012

Add Your Answer

Uploading: 0%

my-video-file.mp4

Complete. Click "Add" to insert your video. Add

×

Loading...
Loading...

Related Questions:

1 Answer

Multiplying monomials raised by a power


Raise each component to the same power
(ax^2y^3z^5)^6=(a^6)(x^12)(y^18)(z^30)

Aug 28, 2014 | Office Equipment & Supplies

1 Answer

If y=f(x)=5x+3/4x-5 , show that x=f(y)


Write the equality in the form y=(5X+3)/(4X-5). Insert parentheses to ensure a correct result.
  1. Multiply both sides of the equality by (4X-5). This gives (4X-5)y=(5X+3).
  2. Open the parentheses as 4Xy-5y=5X+3
  3. Subtract 5X from both sides 4Xy-5y-5X=5X-5X+3
  4. Add 5y to both sides 4Xy-5X-5y+5y=5y+3 or 4Xy-5X=5y+3
  5. Factor the X on the left side X(4y-5)=5y+3
  6. If 4y-5 does not vanish, you can isolate X by dividing both members of the equality by (4y-5).
  7. You get X=(5y+3)/(4y-5)=f(y)
Compare the initial function f(x) and the function just found: They have the same form: X and y have switched places.

Jun 24, 2012 | Mathsoft StudyWorks! Mathematics Deluxe...

2 Answers

Tom is 5 times as old as todd.In seven years Tom's age will be 6 years more than 3 times as old as Todd. How old is Todd


Todd is 4 years old.

Let Tom's age = X
Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )
X+13 = 3Y + 21
X = 3Y + 8

So if:
X=5Y
and
X=3Y+8

Then:
5Y=3Y+8
2Y=8
Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

1 Answer

Michael buys two bags of chips and three boxes of pretzels for 413. He then buys another bag of chips and two boxes of pretzels for 239. Find the cost of each bag of chips and each box of pretzels.


Price of bag of chips s X and price of box of pretzels is Y.
Now you can write following equations:

2X+3Y=413
X+2Y=239

From second equation you know that X is 239-2Y, and you put that in first equation:

2*(239-2Y)+3Y=413

or

-4Y+3Y=413-2*239

Finally we have for Y: Y=65 and X=239-2Y=109.

Aug 13, 2011 | Office Equipment & Supplies

2 Answers

2x - 4y = 20 4x + 2y = -20


This should start wit X=something and Y=something, sorry I'm not an human algebra calculator....

Jul 29, 2011 | Computers & Internet

1 Answer

Definition of special product in algebra types and example of special product in algebra


Product means the result you get after multiplying.
In Algebra xy means x multiplied by y
Likewise when you see (a+b)(a-b) it means (a+b) multiplied by (a-b), which we will be using a lot here!
Special Binomial Products So when you multiply binomials you get ... Binomial Products
And we are going to look at three special cases of multiplying binomials ... so they are Special Binomial Products.
1. Multiplying a Binomial by Itself What happens when you square a binomial (in other words, multiply it by itself) .. ?

(a+b)2 = (a+b)(a+b) = ... ?

The result:

(a+b)2 = a2 + 2ab + b2
You can easily see why it works, in this diagram:

x-y-2-diagram.gif
2. Subtract Times Subtract And what happens if you square a binomial with a minus inside?

(a-b)2 = (a-b)(a-b) = ... ?

The result:

(a-b)2 = a2 - 2ab + b2
3. Add Times Subtract And then there is one more special case... what if you multiply (a+b) by (a-b) ?

(a+b)(a-b) = ... ?

The result:

(a+b)(a-b) = a2 - b2
That was interesting! It ended up very simple.
And it is called the "difference of two squares" (the two squares are a2 and b2).
This illustration may help you see why it works:
apb-amb-why.gif a2 - b2 is equal to (a+b)(a-b) Note: it does not matter if (a-b) comes first:

(a-b)(a+b) = a2 - b2
The Three Cases Here are the three results we just got:
(a+b)2 = a2 + 2ab + b2 } (the "perfect square trinomials") (a-b)2 = a2 - 2ab + b2 (a+b)(a-b) = a2 - b2 (the "difference of squares") Remember those patterns, they will save you time and help you solve many algebra puzzles.
Using Them So far we have just used "a" and "b", but they could be anything.
Example: (y+1)2
We can use the (a+b)2 case where "a" is y, and "b" is 1:

(y+1)2 = (y)2 + 2(y)(1) + (1)2 = y2 + 2y + 1

Example: (3x-4)2
We can use the (a-b)2 case where "a" is 3x, and "b" is 4:

(3x-4)2 = (3x)2 - 2(3x)(4) + (4)2 = 9x2 - 24x + 16

Example: (4y+2)(4y-2)
We know that the result will be the difference of two squares, because:

(a+b)(a-b) = a2 - b2
so:

(4y+2)(4y-2) = (4y)2 - (2)2 = 16y2 - 4
Sometimes you can recognize the pattern of the answer:
Example: can you work out which binomials to multiply to get 4x2 - 9
Hmmm... is that the difference of two squares?
Yes! 4x2 is (2x)2, and 9 is (3)2, so we have:

4x2 - 9 = (2x)2 - (3)2
And that can be produced by the difference of squares formula:

(a+b)(a-b) = a2 - b2
Like this ("a" is 2x, and "b" is 3):

(2x+3)(2x-3) = (2x)2 - (3)2 = 4x2 - 9
So the answer is that you can multiply (2x+3) and (2x-3) to get 4x2 - 9

Jul 26, 2011 | Computers & Internet

1 Answer

(2x+3y)(3x+2y)


(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y
= 6x^2 + 4xy - 9xy - 6y^2
= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:
2x by 3x = 6x squared
2x by 2y = 4xy
-3y by 3x = -9xy
-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

2 Answers

How do I solve x and y in the following equations? 5x+3y=6 2x-4y=5 Thank you


You can solve it with following method.

5x+3y=6 2x-4y=5
So 5x=6-3y so 2[(6-3y)/5]-4y=5
So x=(6-3y)/5 so 12-6y-20y=25
so -26y=25-12
so -26y=13
so y= -(1/2)
2x-4y=5
so 2x=5+4y
so 2x=5+4(-1/2)
so 2x=(10-4)/2
so 2x=6/4
so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.
Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

1 Answer

4x+8y=20 -4x+2y=-30


4x+8y=20 || /4
x+2y=5
x=5-2y

-4x+2y=-30 || /2
-2x+y=-15
-2(5-2y)+y=-15
-10+4y+y=-15
5y=-5
y=-1

x=5-2y || y=-1
x=5-2(-1)
x=5+2
x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

Not finding what you are looking for?
Computers & Internet Logo

Related Topics:

15 people viewed this question

Ask a Question

Usually answered in minutes!

Top Computers & Internet Experts

Doctor PC
Doctor PC

Level 3 Expert

7733 Answers

kakima

Level 3 Expert

102366 Answers

David Payne
David Payne

Level 3 Expert

14161 Answers

Are you a Computer and Internet Expert? Answer questions, earn points and help others

Answer questions

Manuals & User Guides

Loading...